Flocculation in Natural and Engineered Environmental Systems - Droppo, Ian (CRC Press, 2009)
Flocculation is a dominant process in aquatic environments, fundamental to water and wastewater treatment systems. Environmental and economic consequences of flocculation include sedimentation and contaminant transport, which can bring about habitat destructions and affect human health via deterioration of source waters. Understanding the production and behavior of flocs is essential for predicting the fate and effects of particulate material in natural aquatic systems and in the operation of engineered systems.